VD_FINDINFO HC / 2015 / 801 vom 18. September 2015 - VD Tribunal cantonal (2015)
OBLIGATION D'ENTRETIEN, MODIFICATION DES CIRCONSTANCES, PROTECTION DE L'UNION CONJUGALE | 176 al. 1 ch. 1 CC, 179 al. 1 CC